A meta-analysis approach for annotation and identification of lncRNAs controlling perirenal fat deposition in suckling lambs - María Alonso-García; Beatriz Gutiérrez-Gil; Rocío Pelayo; Pablo A. S. Fonseca; Héctor Marina; Juan José Arranz; Aroa Suárez-Vega (Animal Biotechnology)
Long non-coding RNAs (lncRNAs) are being studied in farm animals due to their association with traits of economic interest, such as fat deposition. Based on the analysis of perirenal fat transcriptomes, this research explored the relevance of these regulatory elements to fat deposition in suckling lambs. To that end, meta-analysis techniques have been implemented to efficiently characterize and detect differentially expressed transcripts from two different RNA-seq datasets, one including samples of two sheep breeds that differ in fat deposition features, Churra and Assaf (n = 14), and one generated from Assaf suckling lambs with different fat deposition levels (n = 8). The joint analysis of the 22 perirenal fat RNA-seq samples with the FEELnc software allowed the detection of 3953 novel lncRNAs. After the meta-analysis, 251 differentially expressed genes were identified, 21 of which were novel lncRNAs. Additionally, a co-expression analysis revealed that, in suckling lambs, lncRNAs may play a role in controlling angiogenesis and thermogenesis, processes highlighted in relation to high and low fat deposition levels, respectively. Overall, while providing information that could be applied for the improvement of suckling lamb carcass traits, this study offers insights into the biology of perirenal fat deposition regulation in mammals.